A study on prevalence of various mood disorders in patients with multiple sclerosis in South Indian population Chennai, Tamil Nadu - Murugaiyan, Sivaji; Sivaji, Akshaya Rathin; Vijay, A. Marian Jude; Sundaramurthi, Indumathi; Marimuthu, Jawahar (International Journal of Research in Medical Sciences, 2021)
Background: The prevalence of depressive disorders are more common in demyelination diseases like multiple sclerosis. Patients with multiple sclerosis have higher rates of depressive episodes than the general population. It is found that 40-50% incidence reported in many number of previous research studies .The aim is to study the prevalence of various depressive disorders in multiple sclerosis (MS) patient population. Methods: 176 MS patients were randomly selected from neurology outpatient department (OPD) of Tamil Nadu Government Multi Super Specialty Hospital and Rajiv Gandhi Government General Hospital, Chennai, Tamil Nadu, from September 2018 to December 2019. 128 patients were analyzed with the following methods of examinations such as the structured psychiatric clinical interview with diagnostic and statistical manual of mental disorders (DSM)-5 and international classification of diseases (ICD)-10 criteria, Hamilton depression rating scale (HAM-D) scale. Results: Various subtypes of mood disorders were found as follows major depressive disorder (MDD)-4%, MDD with anxiety-6%, pervasive developmental disorders (PDD) mixed-4%, premenstrual dysphoric disorder (PMDD)-8%, MIDD-2% and depressive disorders due to general medical conditions (secondary depression)-22%. In this present study 46% of the MS population were diagnosed with various depressive illness. Conclusions: Early identification and treatment of depressive disorders definitely favour the outcome of MS patients. The coping skills and good social support system play a vital role in the outcome of depressive disorders in MS population in addition to psychopharmacological management.